2023
DOI: 10.1002/bse.3377
|View full text |Cite
|
Sign up to set email alerts
|

Creating shared value through open innovation approaches: Opportunities and challenges for corporate sustainability

Abstract: To date, few researchers have linked open innovation approaches with triple bottom line corporate sustainability objectives in terms of economic, social, and environmental performance. A systematic review suggests that the businesses' collaborative relationships with external consultants or organizations can increase their competitive advantage, as external stakeholders could assist them in the development of sustainable innovations, diversification into different markets, and in the generation of new revenue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 91 publications
0
17
0
2
Order By: Relevance
“…, this study sheds light on the importance of sources of knowledge for sustainable development by confirming the positive effects the impacts of the two sources of knowledge on green innovation outcomes respectively. While the negative effects of open innovation (e.g.,Camilleri et al, 2023;Gomes et al, 2021;Madanaguli et al, 2023), we revealed both internal and external sources of knowledge relate positively to green innovation through an investigation of Chinese heavily-polluted and high energyconsuming industry. As such, this study is a response for the call of quantitative research on open innovation and sustainability(Madanaguli et al, 2023).Secondly and importantly, this study presents a fresh perspective on the examination of the impact of two sources of knowledge on green innovation.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…, this study sheds light on the importance of sources of knowledge for sustainable development by confirming the positive effects the impacts of the two sources of knowledge on green innovation outcomes respectively. While the negative effects of open innovation (e.g.,Camilleri et al, 2023;Gomes et al, 2021;Madanaguli et al, 2023), we revealed both internal and external sources of knowledge relate positively to green innovation through an investigation of Chinese heavily-polluted and high energyconsuming industry. As such, this study is a response for the call of quantitative research on open innovation and sustainability(Madanaguli et al, 2023).Secondly and importantly, this study presents a fresh perspective on the examination of the impact of two sources of knowledge on green innovation.…”
mentioning
confidence: 86%
“…Based on a literature review, Camilleri et al (2023) proposed that external stakeholders can promote sustainable innovations along with risks and uncertainties, such as leakage sensitive information. Empirically and broadly, the findings of the relationship between external sources and innovation outcomes are mixed (Duong et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, papers in C2-9 discuss using digital technologies to build a sustainable supply chain with more agility and resilience (Dolgui et al, 2020;Ivanov, 2020). In fact, block- egy (e.g., Camilleri et al, 2023), which is also linked to Cluster #8 Entrepreneurship.…”
Section: Consulting Literature Across Disciplines and Boundariesmentioning
confidence: 99%
“…For instance, in the field of sustainability research, scholars have aimed to understand specific dimensions such as how some sustainable practices are beneficial for the financial performance of businesses (Bartolacci et al, 2020). These include emerging conversations around business strategy practices (e.g., De Angelis et al, 2023), sustainable strategic management (P. K. Rao & Shukla, 2022), corporate sustainability (Camilleri et al, 2023) and supply chain strategies (Agrawal et al, 2022). These reviews add value.…”
Section: Introductionmentioning
confidence: 99%
“…The seminal notion of creating shared value (CSV) originated from Porter and Kramer's (2011) paper “Creating Shared Value,” published in Harvard Business Review , in which they argued that enterprise should link their core business activities to social issues and the common good by meeting the shared needs of society, communities, economy, and the environment. Despite theoretical opposition to its originality (see Beschorner & Hajduk, 2017; Crane et al, 2014; Strand & Freeman, 2015), recent works have shown that many companies have successfully adopted CSV strategies and achieved desirable results both economically and socially (Alberti & Belfanti, 2019; Camilleri et al, 2023; Fernández‐Gámez et al, 2019; Hules & Xie, 2015; Ilmarinen & Akpinar, 2018; Khurshid & Snell, 2021; Masood et al, 2021; Mühlbacher & Böbel, 2019; Spitzeck & Chapman, 2012; Yang & Yan, 2020; Yelpo & Kubelka, 2019). These studies predominantly adopt the company as the focal object and apply the case study method to demonstrate the promising results of CSV and hence legitimate it at the strategic level for the enterprise.…”
Section: Introductionmentioning
confidence: 99%